Несчастливой любви не бывает: [рассказы] / Г. М. Артемьева ; под ред. О. Аминовой, С. Груздева - Артемьева Галина Марковна (Лабиринты души, 2011)
Экземпляры: аб. (2011) / Инвентарный номер: 47611 / Цена: / Авт.знак: А 86 / ГРНТИ: 17.82.31 / ББК: 84Р6